Pengaruh Store Atmosphere, Price Discount, Dan Shopping Lifestyle Terhadap Impulse Buying Generasi Z Pada Store KKV Tunjungan Plaza Surabaya - Sintha Erika Putri; Acep Samsudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Thes purpose research to the influence of store atmosphere, price discounts, and shopping lifestyle on the impulse buying of generation Z Tunjungan Plaza Surabaya store at the KKV. The variables this research are store atmosphere, price discount, shopping lifestyle as the independent variable and impulse buying as the dependent variable. This study use multiple linear regression analysis as a quantitative tool. In this reaserch, 100 respondents served as the sample size. Sampling used a nonprobability sampling method with purposive sampling technique. The data collection method uses a questionnaire. The results of this research show that store atmosphere, price discounts, and shopping lifestyle simultaneously have a positive and significant influence on impulse buying at the KKV Tunjungan Plaza Surabaya store. The store atmosphere variable partially has no influence on impulse buying at Tunjungan Plaza Surabaya store at the KKV. The price reduction variable at the KKV Tunjungan Plaza Surabaya store relevants and favorably affects impulsive purchases. The shopping lifestyle variable has a favorable and relevants influence on spontaneous purchases at the KKV Tunjungan Plaza Surabaya store.